A comparative evaluation of the estimated radiographic remaining dentin thickness with the actual thickness below deep carious lesions on posterior teeth: An in vitro study - Nouf AL-Jhany; Banin AL-Hawaj; Alanoud AL-Hassan; Zhoor AL-Semrani; Mohammed AL-Bulowey; Shahzeb Ansari (Saudi Dental Journal)
Objective: The remaining dentin thickness (RDT) is the thickness of healthy dentin between the pulpal floor and the roof of the pulp chamber. It is important to be preserved as it provides the pulp with a protection barrier against mechanical injury and inflammatory products. The focus of the study was to develop a validated method to guide dentists and dental students to estimate the RDT before caries excavation by determining the relationship between the radiographic remaining dentin thickness (RRDT) and actual remaining dentin thickness (ARDT). Methods: A total of 30 extracted human teeth were subjected to two-staged experimentation, including exposure to cone beam radiography and measurement of actual remaining dentin after sectioning. RRDT and ARDT were recorded and the difference was statistically analyzed using SPSS. Results: The Wilcoxon Signed rank test revealed that there was a significant difference in the mean values of the estimated difference in dentin thickness (p value ≤ 0.05).However, no significant comparison of estimation was made for individual samples for molars and premolars. Conclusion: Finding a constant relationship between RRDT and ARDT is challenging.